Words in the wind [new tech terms]. - McFedries, P.
This paper introduces a sampling of new terms that are recently being used in the tech sector. There are terms that appear alongside recently invented gadgets and ideas and are used to name or describe these inventions such as the nouse, PPMT (Pre and Post Mail Tension), nanopretenders, and zettatechnology. Other tech terms come in bunches, particularly when some phenomenon is getting a lot of media attention, such as offshoring, nearshoring, and twoshoring.
Keywords: Pre and Post Mail Tension; Linguistics; Nanopretenders; Nearshoring; Nouse; Offshoring; Tech terms; Twoshoring; Zettatechnology